In silico evaluation, characterization, and in vitro anticancer activity of curcumin–nimbin loaded nanoformulation in HCT-116 cell lines - Arumugam Madeswaran; Selvam Tamilazhagan; Sellappan Mohan (BioTechnologia)
Colorectal cancer is one of the most prevalent malignancies worldwide and a leading cause of mortality. Chemotherapy medications are often limited in use due to issues like drug resistance, P-glycoprotein efflux, and relapse of chemotherapy. In this study, we formulated a nanosuspension with curcumin and nimbin to address these limitations and assessed its anticancer potential using in silico molecular docking and in vitro MTT assay. Methods. In silico docking and ADMET analyses targeted proteins implicated in colorectal cancer, with doxorubicin as the standard. The docking studies were conducted using AutoDock 4.2, while in vitro anticancer activity was assessed through the MTT assay in HCT 116 cell lines. Results. In silico docking of curcumin and nimbin showed significant interactions with target proteins compared to the standard. ADMET analysis indicated favorable Caco-2 permeability and intestinal absorption of the selected phytoconstituents. The MTT assay demonstrated concentration-dependent cell viability inhibition in HCT 116 cell lines treated with the nanosuspension, with an IC 50 value of 30%. Conclusion. The curcumin–nimbin loaded nanosuspension demonstrated promising anticancer activity against HCT 116 cell lines in both in silico and in vitro studies. Further studies are required to evaluate the anticancer effect of curcumin–nimbin loaded nanosupension through clinical and preclinical studies for the progress of potential formulation in the treatment of colorectal cancer.